PERBAIKAN DOKUMEN IMPOR TERHADAP ON-TIME CLEARANCE PADA PERUSAHAAN FREIGHT FORWARDING - Noorman Irhamna; Vanessa Aprilian; Erni Pertiwi Perwitasari (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
PT. DHL Global Forwarding is a freight forwarder company which is engaged in freight forwarding, logistics and freight both exports and imports. The issue discussed in this research is the influence of the data repair (redress) to the on-time clearance at PT. DHL Global Forwarding Indonesia in 2015. The purpose of the study was to determine the influence of the data repair (redress) to the on-time clearance. To gain the result, the writers use qualitative methods of Logical Framework Approach (LFA). Writers collected data through observation and interview given to 5 employees as samples. By using the LFA analysis, it is shown that the improvement of data (redress) greatly affects on-time clearance, due to the improvement of data (redress) indicates that the data are subject to rejection so it takes 1-5 days to process correction which means exceeds the Key Performance Indicator (KPI).